Global Lynching and Collective Violence : Volume 2: The Americas and Europe - Pfeifer, Michael J. (Michael James), 1968- (Book collections on Project MUSE., 2017)
In this second volume of the groundbreaking survey, Michael J. Pfeifer edits a collection of essays that illuminates lynching and other extrajudicial "rough justice" as a transnational phenomenon responding to cultural and legal issues. The volume's European-themed topics explore why three communities of medieval people turned to mob violence, and the ways exclusion from formal institutions fueled peasant rough justice in Russia. Essays on Latin America examine how lynching in the United States influenced Brazilian debates on race and informal justice, and how shifts in religious and political power drove lynching in twentieth century Mexico. Finally, scholars delve into English Canadians' use of racist and mob violence to craft identity; the Communist Party's Depression-era campaign against lynching in the United States; and the transnational links that helped form--and later emanated from--Wisconsin's notoriously violent skinhead movement in the late twentieth century.